Answer:
CE = 3
Explanation:
Given:
AE = 3
EB = 4
CE = x
ED = x + 1
Required:
CE
Solution:
First we need to determine the value of x by generating am equation as follows:
CE × ED = AE × EB (Interacting Chords Theorem)
Substitute
x × (x + 1) = 3 × 4
x² + x = 12
Subtract 12 from each side
x² + x - 12 = 12 - 12
x² + x - 12 = 0
Factorize to find the value of x
x² + 4x - 3x - 12 = 0
x(x + 4) -3(x + 4) = 0
(x - 3)(x + 4) = 0
x - 3 = 0
x = 3
Or
x + 4 = 0
x = -4
Let's use the positive value of x
CE = x = 3